The effect of Epstein–Barr virus viremia on the progression to severe COVID-19. Issue 18 (6th May 2022) - Im, Jae Hyoung; Nahm, Chung Hyun; Je, Young Soo; Lee, Jin-Soo; Baek, Ji Hyeon; Kwon, Hea Yoon; Chung, Moon-Hyun; Jang, Ji-Hun; Kim, Jung Soo; Lim, Jun Hyeok; Park, Mi Hwa
Abstract : Abstract: Epstein–Barr virus (EBV) is frequently reactivated by coronavirus 2019 (COVID-19), and a high incidence of EBV viremia has been reported in patients with severe COVID-19. However, the impact of EBV viremia on progression to severe COVID-19 is unclear. Therefore, we conducted a study to evaluate the effect of EBV on COVID-19 progression. We investigated EBV viremia at the time of admission in COVID-19 patients hospitalized between February 1, 2020, and April 11, 2021. A cross-sectional study was performed to compare the severity of COVID-19 according to the presence or absence of EBV viremia. However, since it is difficult to analyze the influence of EBV viremia on COVID-19 progression with cross-sectional studies, a retrospective cohort study, limited to patients with mild COVID-19, was additionally conducted to observe progression to severe COVID-19 according to the presence or absence of EBV viremia. Two hundred sixty-nine COVID-19 patients were tested for EBV viremia. In a cross-sectional study that included patients with both mild and severe COVID-19, the EBV viremia group had more severe pneumonia than the EBV-negative group. However, in the cohort study limited to mild cases (N = 213), EBV viremia was not associated with COVID-19 progression. COVID-19 severity may affect EBV viremia; however, there was no evidence that EBV viremia was a factor in exacerbating pneumonia in patients with mild COVID-19.